4-Methyl-2,3-dihydro-1H-1,5-benzodiazepin-2-one monohydrate - Saber, A.; Zouihri, H.; Essassi, E.M.; Ng, S.W. (International Union of Crystallography, 2010)
The seven-membered fused-ring in the title compound, C(10)H(10)N(2)O center dot H(2)O, adopts a boat conformation (with the two phenylene C atoms representing the stern and the methylene C atom the prow). In the crystal, two benzodiazepinone molecules are linked about a center of inversion by diazepine-carbonyl N-H center dot center dot center dot O hydrogen bonds. The dimers are further linked by water-diazepine O-H center dot center dot center dot N hydrogen bonds, forming a linear chain.